(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
As the demand for sustainable and efficient energy sources increases, integrating solar power into UAV operations presents a viable solution. Conventional MPPT controllers for solar-powered UAVs suffer from slow response times and inefficiencies under dynamic environmental conditions. This study proposes an enhanced power management system integrating FLC with MPPT for superior energy efficiency. The proposed power management design is achieved with the implementation of the Perturb and Observe (P and O) algorithm coupled with a Proportional-Integral (PI) controller to achieve Maximum Power Point Tracking (MPPT). The P&O algorithm was chosen for its simplicity and widespread adoption in MPPT applications, while PI control ensures stable convergence to the MPP. The integration of FLC further improves adaptability in fluctuating irradiance conditions. This approach ensures that the UAV operates at optimal power output levels under varying environmental conditions, specifically temperature solar irradiance. Additionally, a Fuzzy Logic Control (FLC) mechanism is employed to dynamically adjust the power output based on real-time data, ensuring optimal performance and stability. The results gotten from the simulations show that the FLC and the PI based on P & O algorithm returned a settling time of 0.01 seconds and 0.45 seconds respectively. The result showed that the fuzzy logic controller achieved a settling time 97% faster than the PI based on P & O algorithm. This research contributes to the development of more sustainable UAV technologies, paving the way for broader applications in various fields, including environmental monitoring and disaster response.